2014
DOI: 10.1016/j.jjcc.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of everolimus versus other rapamycin derivative-eluting stents on clinical outcomes in patients with coronary artery disease: A meta-analysis of 16 randomized trials

Abstract: EES is associated with a significant reduction in definite ST and TLR for treating patients with coronary artery disease, compared with a pooled group of other rapamycin derivative-eluting stents. Biolimus-eluting stent had similar safety and efficacy for treating patients with coronary artery disease, compared with the EES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…[ 16 ] A pooled analysis from the SPIRIT II, III, IV, and COMPARE trials also showed that EES significantly reduced composite endpoint of cardiac death/MI/ischemia-driven target lesion revascularization compared with the old generation DES. [ 6 ] In this analysis, we demonstrated a consistent low risk of ST, TVF, and NACE in patients following EES implantation at 2-year follow-up.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…[ 16 ] A pooled analysis from the SPIRIT II, III, IV, and COMPARE trials also showed that EES significantly reduced composite endpoint of cardiac death/MI/ischemia-driven target lesion revascularization compared with the old generation DES. [ 6 ] In this analysis, we demonstrated a consistent low risk of ST, TVF, and NACE in patients following EES implantation at 2-year follow-up.…”
Section: Discussionsupporting
confidence: 54%
“…or biodegradable polymers offer better safety outcomes. [ 6 ] The “all-comers” COMPARE (Comparison of the everolimus eluting XIENCE-V stent with the paclitaxel eluting TAXUS LIBERTE stent in all-comers: a randomized open label trial) trial showed EES was associated with a significant reduction in definite/probable ST compared with paclitaxel-eluting stent (0.6% vs. 2.5%, P < 0.001) at 2 years follow-up. [ 15 ] Recently, a large registry study found that EES had a lower risk of very late ST (2.0%) than sirolimus-eluting stent (2.8%, P = 0.05) and paclitaxel-eluting stent (4.0%, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy calcification, another big challenge to the operator, increases the likelihood of procedural failure and complications in coronary intervention. [ 19 , 20 ] In the present study, 75 (37%) of 188 complex cases involved heavy calcification lesions and were completed successfully. Rotational atherectomy was used through radial artery access in 2 cases; the 1.25 and 1.5 mm burr can be used through the 6F catheter thereby easily achieving plaque modification in most cases.…”
Section: Discussionmentioning
confidence: 61%
“…One of the biggest differences between studied devices is the type of antiproliferative drug eluted from the stent surface (sirolimus vs. everolimus). Safety data from large meta-analysis favor the use of everolimus vs. sirolimus eluting stents [38]. However, most of the differences in device performance are explained by the type and design of metallic platforms or polymers used in these devices.…”
Section: Discussionmentioning
confidence: 99%